Pure Theories of Policy Mix: Nordhaus's Destructive Game and the Case of High Inflation - Le Page, Jean-Marie (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2024)
Nordhaus’s theory of the “destructive game” (1994) is a central analysis of the policy mix. His theory showed that a lack of cooperation between the central bank and the fiscal authorities would result in the budget deficit being higher and the inflation rate lower than either of the authorities would want. It explains indeed why Central Bank independence can lead to these suboptimal results even when the goals of monetary policy are set by the fiscal authority. But the construction of this model was based on the existence of a Phillips-type relationship between the inflation rate and the unemployment rate, which has lost its relevance in the contemporary economy. Today, the prospect of a rise in the inflation rate leads to an increase in interest rates and a subsequent rise in the unemployment rate. This paper intends to show that the main conclusions of the Nordhaus model are preserved, with a model based on an increasing relationship between the inflation rate and the unemployment rate. Moreover, as in traditional macroeconomic theory, according to this version of the model, the unemployment rate is the same in steady states for different strategic equilibria.